BANGUNAN KUNO WISMA PERDAMAIAN DALAM SEJARAH KOTA KAWASAN SIMPANG TUGU MUDA, SEMARANG - Ahmad Zuhdi Allam; Meilani Martini; Muhammad Irwansyah; Liza O. Tutuarima (Universitas Katolik Soegijapranata, 2022)
Abstract The Simpang Tugu Muda Area has great significance for Semarang City. In this area, several buildings have become landmarks of this city. Unfortunately, the history of this area has not been written systematically, and among the historical landmarks in this area, the Old Building of Wisma Perdamaian has the most confusing history. This article was based on the 2021 historical research in the Simpang Tugu Muda Area and describes its history and the Old Building of Wisma Perdamaian based on a more factual data; therefore, it can contribute to build a more solid history of Semarang City and architectural conservation efforts there. This research used a historical research method as well as field observation. One of the research findings shows that the Old Building of Wisma Perdamaian was not the residence of the Governor of the North Coast of Java Verenigde Oostindische Compagnie (VOC) in the 18th century, as many people believe. This building was built by Koninklijk Nederlands Indisch Leger (KNIL) as the residence of the Major General of the KNIL in the 19th century. Meanwhile, the residence of the Governor of the North Coast of Java, VOC, was demolished in 1908.Keywords: History of architecture and the city, Semarang, Tugu Muda Area, Wisma Perdamaian AbstrakKawasan Simpang Tugu Muda memiliki signifikansi yang besar di Kota Semarang. Di kawasan ini berdiri pula beberapa bangunan yang menjadi tengaran kota ini. Di antara bangunan-bangunan tersebut, Bangunan Kuno Wisma Perdamaian memiliki sejarah yang paling simpang siur. Artikel ini ditulis berdasarkan penelitian historis Kawasan Simpang Tugu Muda yang dilaksanakan pada 2021 dengan tujuan untuk memaparkan sejarah arsitektur dan tata kota kawasan ini dan Bangunan Kuno Wisma Perdamaian berdasarkan data primer yang lebih faktual, sehingga diharapkan dapat berkontribusi pada penulisan sejarah dan pelestarian arsitektur di Kota Semarang yang lebih solid. Metode yang dipakai dalam penelitian ini adalah metode penelitian sejarah yang dilengkapi dengan observasi lapangan. Salah satu temuan penelitian menunjukkan bahwa Bangunan Kuno Wisma Perdamaian bukanlah kediaman Gubernur Pantai Utara Jawa Verenigde Oostindische Compagnie (VOC) pada abad ke-18 seperti yang diyakini banyak orang. Bangunan ini dibangun oleh Koninklijk Nederlands Indisch Leger (KNIL) sebagai kediaman Mayor Jenderal KNIL pada abad ke-19. Sementara kediaman Gubernur Pantai Utara Jawa VOC sudah dirobohkan pada 1908.Kata kunci: Sejarah Arsitektur Kota, Semarang, Simpang Tugu Muda, Wisma Perdamaian